Procedural Content Generation in Games towards Semantic Web - Vashistha, VK; Malik, SK (International Journal of Computer Sciences and Engineering, 2025)
Procedural Content Generation (PCG) : A significant research area in the domain of digital games, which provides techniques to automatically generate game content such as levels, narratives, landscape, game rules and mechanics, etc. without or with least human effort. In these days, video games are usually backed by web services in order to fetch game content directly from game servers rather than storing everything at client side, for better controllability over the game content. Semantic Web technologies play an important role in World Wide Web (WWW) with the objectives to ¬create and maintain structured Web of Data to make it more machine understandable. Potentially, Semantic Web may contribute to PCG by enhancing its capabilities in terms of computational creativity, better algorithmic efficiency, scalability, interoperability etc. In this paper, first, the role of PCG and Semantic Web in games has been explored. Second, a Semantic Based PCG Framework has been proposed, which combines strength of both the fields and exploit the content of existing knowledge repositories such as DBPedia, WordNet, Freebase, etc. to generate interesting puzzles. Third, proposed framework has been supported by taking the case study of a popular word game Hangman. Finally, emphasis on exploring various concerns is made towards the role of Semantic Web in procedural content generation in games.